Swat modelling of streamflow and sediment concentration in an amazonian basin impacted by artisanal gold mining - Camila Andrade Abe (2017)
Land cover change such as replacing the forest with pasture or bare soil areas can significantly affect the water cycle, altering streamflow regime, accelerating or intensifying erosive processes and influencing water quality and availability. In Crepori River basin, the expansion of gold mining activity has caused an increase in sediment concentration in the river. Sediment concentration in rivers can be quantified using direct or indirect methods, but it is usually difficult to quantify sediment generated by point and non-point sources, such as mining activities and land cover, respectively. In this study, SWAT model (Soil and Water Assessment Tool) was applied in Crepori basin, from 2001 to 2012 to investigate the impacts of land cover change on streamflow regime and on sediment concentration in the river. By comparing simulated sediment concentration and sediment concentration estimated via remote sensing by Lobo et al. (2015) for the same region, this study aimed to define the proportion of sediment concentration due to sheet erosion (non-point source) from that of gold mining activities (point source) in Lobo et al. (2015) estimates. Results show a good adjustment of the model for streamflow (NSE = 0.84, PBIAS = -2.44%, RSR = 0.40) and simulated sediment concentration corresponds to measured values from published studies for period and regions with low or no mining activity. Simulations indicate that land cover change occurred between 2001 and 2012 in Crepori basin were not sufficient to significantly impact the river streamflow, but simulations performed for different scenarios of land cover (referring to the periods of 1973, 1998-2010, a future scenario of 2040 and a hypothetical scenario of complete soil exposure) showed a trend in increasing streamflow given the increase in deforested and bare soil areas in the Basin. Regarding sediments, in average, 14% of sediment concentration estimated by Lobo et al. (2015) in high-water season corresponds to sediment generated by diffuse soil erosion, whereas this average proportion is of 6% in the low-water season. Results also showed that seasonality of sediment concentration generated only due to diffuse soil erosion is the inverse of that observed by Lobo et al. (2015), which includes mining activity. Finally, the increase in deforested and bare soil areas in the basin are associated to the increase in sediment concentration in both wet and dry periods, and the simulations for the hypothetical bare soil scenario indicate that the effects of mining activity on sediment concentration in Crepori River may surpass expected impacts of the scenario with maximum soil exposure to pluvial erosion.